Repetition of misoriented words reduces lexical-decision response times at repeated and novel orientations. - Jordan, Kevin; Huntsman, Laree A. (Journal of Experimental Psychology. Human Perception & Performance, 1995)
Participants made lexical decisions about misoriented 4-letter or 6-letter strings. Misorientation effects on response times diminished quickly in a condition where a small set of words was repeated many times. However, misorientation effects persisted with a large set of words where no word was repeated. Experiment 1 also demonstrated that misorientation had a larger effect on 6-letter words than on 4-letter words. This might indicate that misorientation forces letter-by-letter, rather than parallel, processing of a word's constituent letters. Experiment 2 demonstrated that only 1 repetition of a word was needed to produce a significant reduction in misorientation effects. Furthermore, this reduction generalized completely to the same word presented 60° from the initial orientation. The results can be described by automatic broad-orientation tuning of new representations rather than by mental rotation to a new representation. Reprinted by permission of the publisher.